The attentional 'zoom‐lens' in 8‐month‐old infants. Issue 1 (20th February 2015) - Ronconi, Luca; Franchin, Laura; Valenza, Eloisa; Gori, Simone; Facoetti, Andrea
Abstract: The spatial attention mechanisms of orienting and zooming cooperate to properly select visual information from the environment and plan eye movements accordingly. Despite the fact that orienting ability has been extensively studied in infancy, the zooming mechanism – namely, the ability to distribute the attentional resources to a small or large portion of the visual field – has never been tested before. The aim of the present study was to evaluate the attentional zooming abilities of 8‐month‐old infants. An eye‐tracker device was employed to measure the saccadic latencies (SLs) at the onset of a visual target displayed at two eccentricities. The size of the more eccentric target was adjusted in order to counteract the effect of cortical magnification. Before the target display, attentional resources were automatically focused (zoom‐in) or spread out (zoom‐out) by using a small or large cue, respectively. Two different cue–target intervals were also employed to measure the time course of this attentional mechanism. The results showed that infants' SLs varied as a function of the cue size. Moreover, a clear time course emerged, demonstrating that infants can rapidly adjust the attentional focus size during a pre‐saccadic temporal window. These findings could serve as an early marker for neurodevelopmental disorders associated with attentional zooming dysfunction such as autism and dyslexia. Abstract : Despite the fact that attentional orienting has been extensively studied in infancy, the zooming mechanism ‐‐ namely, the ability to distribute the attentional resources to a small or large portion of the visual field ‐‐ has never been tested before. Our results demonstrated, for the first time, that 8‐month‐old infants can rapidly adjust the attentional focus size during a pre‐saccadic temporal window.